Printable Thermoelectric Materials and Applications - Liu, Xiaowei; Wang, Ziyu (Frontiers in Materials, 2019)
Thermoelectric (TE) materials have been of great importance for the capability of direct energy conversion between heat and electricity. In the past decades, people have developed various methods to enhance the performance of TE materials, which is characterized in terms of the dimensionless figure of merit of ZT. Combined with the advanced techniques of printing, the printable and flexible TE materials have been obtained, which can greatly broaden the application of the TE materials, thus improve the overall energy conversion efficiency. Most importantly, the flexible high performance TE materials-based device can reduce the consume of unrecoverable resources. In this review, we would like to discuss the strategies of enhancing the performance of TE materials. Then, the advanced techniques of printing of TE materials-based device will be involved. Finally, we would suggest some promising materials to enhance the thermoelectric performance and the potential applications in future.